Development And Testing Of Conflict Management Training Module For Counsellors - Asmah Ismail (Universiti Sains Islam Malaysia, 2024)
This study was to determine the counsellor trainee’s needs in managing conflict in group counselling, and to develop and test a conflict management training module. The study applied the sequential exploratory research design by combining the phenomenological approach with the one-group pretest-posttest experimental design. The phenomenological approach explored the trainees’ experience with conflict and group leadership functions while the second design assessed the effects of the training module. To collect phenomenological data, semi-structered interviews were conducted with 12 subjects (female=8, male=4, mean age=27.3) from the Guidance and Counseling graduate program. The interview data was analysed using the phenomenological analysis to identify the themes and subthemes which were used to develop a conflict management training module. The module consisted of six 2-hour sessions focusing on group leadership functions, conflicts, and conflict management strategies. The module has content validity of .80. To test the module effects, a set of questionnaires was developed and administered before and after the execution of the training module. A pilot test on the questionnaires showed that the validity coefficients were from .84 to .93 and the reliability coefficients range from .62 to .88, thus providing evidence that the instruments are of good validity and reliability. Thirty one graduate students (female=24, male=7, mean age=28.4) from the Guidance and Counselling program were chosen through simple random sampling to participate in the training workshop. The quantitative data was analysed using the inferential statistics, the paired-sample t-test. The significant level was set at .05. The results from the pretest and posttest scores show significant increment after the trainees completed the module. They report gaining more knowledge on conflicts (t(30)= 17.977, p≤.05), becoming competent at managing conflicts (t(30)= 17.422, p≤.05), and having more favourable attitude towards conflict (t(30)= 7.655, p≤.05) and towards group leadership functions (t(30)= 7.712, p≤.05). The study proposes that future research explores the gender and cultural influences on the concept of leadership in group counselling and conflict management strategies, It also suggests that training and supervision be made available for counsellor trainees and counsellors in general to continuously upgrade their group skills, in particular intervention skills to manage conflict constructively.